2017
DOI: 10.1371/journal.pone.0169839
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Social Media Use: Results from a Large-Scale Nationally Representative Adolescent Sample

Abstract: Despite social media use being one of the most popular activities among adolescents, prevalence estimates among teenage samples of social media (problematic) use are lacking in the field. The present study surveyed a nationally representative Hungarian sample comprising 5,961 adolescents as part of the European School Survey Project on Alcohol and Other Drugs (ESPAD). Using the Bergen Social Media Addiction Scale (BSMAS) and based on latent profile analysis, 4.5% of the adolescents belonged to the at-risk grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
539
4
28

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 654 publications
(607 citation statements)
references
References 54 publications
36
539
4
28
Order By: Relevance
“…PSMU is a complex phenomenon and is influenced by many factors and has been conceptualized in various ways (Bányai et al 2017), including as being sub-type of internet addiction Young 2015). Similar to behavioral and chemical addictions, people with PSMU show uncontrolled and compulsive behaviors (Griffiths 2005(Griffiths , 2010.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMU is a complex phenomenon and is influenced by many factors and has been conceptualized in various ways (Bányai et al 2017), including as being sub-type of internet addiction Young 2015). Similar to behavioral and chemical addictions, people with PSMU show uncontrolled and compulsive behaviors (Griffiths 2005(Griffiths , 2010.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
“…In the literature, PSMU has been investigated in relation to specific SMSs such as Facebook (Andreassen et al 2012;Hong et al 2014), Twitter (Davenport et al 2014;Kircaburun 2016a;Kim et al 2008), Instagram (Kircaburun and Griffiths 2018a, b), Snapchat (Punyanunt-Carter et al 2017), WeChat (Hou et al 2017), Youtube (Balakrishnan and Griffiths 2017), and social media in general (Andreassen et al 2017;Bányai et al 2017;Kircaburun 2016b;Kircaburun et al 2018a, b). These studies have shown that PSMU is associated with various psychological, personality, and individual difference factors.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
“…Individuals' impetus to seek out long-term satisfying relationships can be a motivation for their emotions, thoughts, and behaviors. Because short-term relationships do not satisfy human beings in the long run, individuals seek out relationships that meet their need of belonging (Baumeister and Leary 1995). Individuals, who have the need to live in a community, may also satisfy their need for a safe and predictable community environment via social media sites .…”
Section: Social Connectedness and Belongingnessmentioning
confidence: 99%
“…Furthermore, neither the CPUI nor PPUS included all of the potential dimensions of problematic pornography use (i.e., withdrawal or relapse). The present study aimed to fill this gap by using a deductive strategy and Griffiths ' (2005) components model in order to assess problematic online pornography use because it has been used in the development of many psychometrically robust instruments assessing excessive problematic behavior including social networking (Bányai et al, 2017), gaming (Lemmens, Valkenburg, & Peter, 2009), exercise (Terry et al, 2004), shopping (Andreassen et al, 2015), television series watching , work (Andreassen et al, 2012) and use of Tinder (Orosz, Tóth-Király, Bőthe, & Melher, 2016). Furthermore, neither the CPUI nor PPUS included all of the potential dimensions of problematic pornography use (i.e., withdrawal or relapse).…”
Section: Introductionmentioning
confidence: 99%